Ecological modernisation theory and the changing dynamics of the European automotive industry: the case of Dutch end-of-life vehicle policies. (24th February 2004) - Smink, Carla K.; van Koppen, C.S.A. (Kris); Spaargaren, Gert
In this article, we use ecological modernisation theory to analyse environmental changes in the car chain. We do not intend to cover all environmental aspects of car production and consumption. The focus will be on the handling of cars in the waste phase. We are interested in the interaction between technology and policy. We argue that some technological developments in handling end-of-life vehicles trigger policy questions. But also the other way around: some policy styles favour some development paths of end-of-life vehicle technologies and foreclose others. By this combined treatment of technological and political issues, we hope to contribute to the discussion on the overall organisation of the ELV-dimension of car chains in the future. We have chosen to deepen our understanding of the basic characteristics of the ecological modernisation process in car chains by looking in some detail at the Dutch ELV-economy in the period 1970–2000 and beyond.